The Experience Economy in the Systems of Urban and Regional Transport - from a Change of Location to Positive Emotional Impressions during Movements - Gnap, Jozef; Dydkowski, Grzegorz; Urbanek, Anna (Communications - Scientific Letters of the University of Zilina, 2024)
The achievements of the experience economy show that, when using services, not only their useful value is important, i.e., changing the location in the case of transport, but also related positive experiences and impressions are of increasingly great importance. Hence, the aim of the research was to assess and indicate the directions of application possibilities of the experience economy in the urban and regional transport. There were used methods of analysis of the current theoretical achievements of the experience economy and the social studies into the use of cars, as well as the methods of analogy, brainstorming, synthesis, and modelling. The personalization of services should be pursued, in the field of passenger information, travel planning, and tariff solutions, as well as solutions increasing the possibility of using the travel time for the professional matters, education, and entertainment.
Keywords: public transport; urban and regional transport development of services; experience economy